2013
DOI: 10.1002/ptr.4908
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and In Vitro Anticancer Effect of 2‐Pyrrolidinone Rich Fraction of Brassica oleracea var. capitata Through Induction of Apoptosis in Human Cancer Cells

Abstract: The aim of this study was to analyze if the 2-pyrrolidinone rich fraction of Brassica oleracea var. capitata exhibiting antioxidant and in vitro anticancer activities. 2-Pyrrolidinone is an active compound present in Brassica oleracea var. capitata. Our findings explored the potential use of 2-pyrrolidinone in cancer treatment. This compound was identified and isolated by gas chromatography-mass spectrometry and high-performance liquid chromatography from the leaf of Brassica oleracea var. capitata. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 21 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…A further protective effect of Brassicaceae is represented by the inhibition of mechanisms regulating the development of cancer. Indeed, a 2-pyrrolidinone rich extract from Brassica oleracea showed in vitro cytotoxicity on HeLa and PC-3 human cancer cell lines, and it also exhibited antioxidant activity in a cell-free system [ 39 ]. Adverse effects of compounds that are present in Brassicaceae towards metabolic syndromes are also possible.…”
Section: Bioactive Compounds In Brassicaceae Anmentioning
confidence: 99%
“…A further protective effect of Brassicaceae is represented by the inhibition of mechanisms regulating the development of cancer. Indeed, a 2-pyrrolidinone rich extract from Brassica oleracea showed in vitro cytotoxicity on HeLa and PC-3 human cancer cell lines, and it also exhibited antioxidant activity in a cell-free system [ 39 ]. Adverse effects of compounds that are present in Brassicaceae towards metabolic syndromes are also possible.…”
Section: Bioactive Compounds In Brassicaceae Anmentioning
confidence: 99%
“…These include: 9, 12-octadecadienoic acid (Z,Z)-(0.83%), a conjugated linoleic acid reported to occur in an ethanolic extract of Phragmytes vallatoria leaves; 32 2-pyrrolidinone (0.38%), reported in Brassica oleraceae var. capitata; 33 Vitamin-E (0.32%), a potential antioxidant that protects the cell against free radicals; 28,31 hexadecanoic acid methyl ester (0.23%), that has been detected in the methanolic fraction of Aegle marmelos 31 and a well-reported antioxidant compound, retinol (0.17%), that inhibits lipid peroxidation. 34 Thus, 11% of the phytoconstituents identified in the ethanolic extract of T. divaricata leaves in the current study have previously been reported to exhibit antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…The hypocholesterolemic effect of eggplant has been well documented in addition to its rich content of iron, calcium, potassium, phosphorus, and vitamin B complex [82,83]. Broccoli is a good source of quercetin, sulforaphane, and polyphenolic antioxidants, and may offer help in reducing cholesterol and regulating insulin [84][85][86]. Carrot, usually eaten raw or as a cooked vegetable, may be artery protecting, immunomodulating, and hypocholesterolemic [87,88].…”
Section: Rosmentioning
confidence: 99%